Expansion of Full-Day Childcare and Subjective Well-Being of Mothers: Interdependencies with Culture and Resources - Pia S. Schober; Juliane F. Stahl (European Sociological Review, 2016)
This study investigates whether an expansion of state-subsidized full-day childcare may improve the subjective well-being of mothers of children under school age by acting as a boundary-spanning resource to facilitate the combination of employment and childcare responsibilities. It extends previous studies which showed contradictory results by demonstrating that the relationship with parental subjective well-being may vary by local work-care culture and family resources. To this effect, we compare mothers in East and West Germany and mothers with and without a partner in the household, respectively. The empirical analysis links individual-level data from the Socio-Economic Panel for 2007 to 2012 and from the 'Families in Germany'-Study for 2010 to 2012 with administrative records on day-care provision at the county level. We apply fixed-effects panel models to samples of 3,203 families with a youngest child under school age. Our results show that greater provision of full-day care is modestly positively associated with satisfaction with family life and with life overall among partnered mothers in East Germany but not in West Germany. The level of full-day care availability in a county and take-up of full-day childcare, however, moderate the relationship of maternal transitions to long part-time or full-time employment with satisfaction with family life in West Germany. In both East and West Germany, switching to full-day care for the youngest child is more positively associated with satisfaction with family life for lone mothers than for partnered mothers.
Additional information: Supplementary Data: https://academic.oup.com/esr/article/32/5/593/2197562#supplementary-data
Keywords: 330